Psychological Security and Social Intelligence in Adolescents and Young People - Baeva I.A; Gayazova L.A; Kondakova I.V; Laktionova E.B (Moscow State University of Psychology and Education, 2021)
The paper presents results of a study on the relationship between the level of students' psychological security in educational environment and their social intelligence.The aim of the study was to redefine this relationship and to test the hypothesis that different levels of psychological security in educational environment are connected with changes in the level of social intelligence and its components that happen in adolescence and young age.The data was obtained on a sample of students of secondary-level vocational training organizations (n=2,789 subjects) aged 12-25 years (M=17.13), 71,89% males.The following techniques were used: "Psychological Safety of Educational Environment" by I.А.Baeva; "The Tromsø Social Intelligence Scale" (TSIS) by D.H.Silvera, M.Martinussen, T.I.Dahl; sociodemographic information questionnaire.The study revealed that the level of social intelligence was higher among the students with high levels of psychological security in educational environment (U=114,56; p≤0,001).Higher social intelligence levels are based on the ability to understand and predict other people's behaviours and feelings (U=101,25; p≤0,001) as well as on social skills (U=97,74; p≤0,001), whereas social awareness levels are the same in environments with different levels of psychological security.